2019
DOI: 10.1097/bot.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparative Cohort Study Comparing Temporary Internal Fixation to External Fixation at the First Stage Debridement in the Treatment of Type IIIB Open Diaphyseal Tibial Fractures

Abstract: Objectives: To compare the rates of deep infection, flap failure and nonunion after temporary internal fixation (TIF), with temporary external fixation (ex-fix) in the management of Gustilo-Anderson (GA) type IIIB open tibia fractures. Design: Retrospective comparative cohort. Setting: Level 1 trauma center. Patients/Participants: 64 consecutive patients with a GA type IIIB open diaphyseal tibia fracture (OTA/AO 42) were treated between May 2014 and May 2016. 47 patients (TIF = 24; ex-fix = 23) met the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
0
20
2
Order By: Relevance
“…External fixation as a temporizing measure has ceased to exist as part of the novel ortho-plastic protocol in the study unit. [9] This has been the case since May 2015, one year prior to the end period of the study. Patients prior to this novel protocol received external fixation.…”
Section: Surgical Interventionsmentioning
confidence: 95%
See 1 more Smart Citation
“…External fixation as a temporizing measure has ceased to exist as part of the novel ortho-plastic protocol in the study unit. [9] This has been the case since May 2015, one year prior to the end period of the study. Patients prior to this novel protocol received external fixation.…”
Section: Surgical Interventionsmentioning
confidence: 95%
“…Use of the plate is a very simple technique that encourages adequate exposure of the zone of injury. [9,12] All wounds, regardless of type of temporary fixation, were dressed with negative pressure wound therapy (NPWT) and this is not removed until the second stage. Following stage one, the patient is physiologically stabilised until definitive fixation and soft tissue coverage, This is then undertaken on a dedicated ortho-plastics operating list.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…reported that the infection rate was significantly lower in patients in whom the wound was closed within 5 days of the injury [ 7 ]. Nevertheless, only a limited number of reports have evaluated how to cover lost soft tissue to increase the success rate of reconstruction [ 11 , 12 ]. While treatment with antibiotics is recommended 24–72 h after wound closure [ 13 ], only a few reports have focused on antibiotic prophylaxis in open fractures [ 8 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bone ends are delivered, debrided and irrigated with a minimum of 5 litres of normal saline. The fracture is provisionally stabilised using a 3.5mm dynamic compression plate (DCP) as temporary internal fixation (TIF) (13). This is applied with transcoritcal screw fixation most commonly to the anteriomedial tibia.…”
Section: Surgical Interventionsmentioning
confidence: 99%
“…Control and Prevention (CDC) for 'deep incision surgical site infection', see Figure , Supplemental Digital Content 1, http://links.lww.com/JOT/A985 (16). The definition was not reliant on positive cultures, and assumed that any surgical debridement, revision or antibiotic use within this cohort was indicative of deep infection (3,13).…”
Section: Diagnosis Of Deep Infection Was Based On Criteria Described By the Centers For Diseasementioning
confidence: 99%